Data on the Outside versus Data on the Inside. - HELLAND, PAT (Communications of the ACM, 2020)
The author discusses the differences between computer data within a service and data that is transmitted outside a service boundary. It examines the structure of data, and the benefits and drawbacks of the computer programming languages Structure Query Language (SQL) and JavaScript Object Notation.